2021
DOI: 10.1111/jce.15114
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long‐term success after catheter ablation of premature ventricular complexes

Abstract: Introduction: Some patients have late recurrence after acutely successful radiofrequency catheter ablation (RFCA) of premature ventricular complexes (PVCs). The aim of this study was to evaluate predictors of long-term success following acutely successful PVC RFCA. Methods:We identified consecutive patients at our institution with frequent PVCs undergoing RFCA and reviewed procedural data and medical records. Acute success was defined as elimination of targeted PVCs for at least 30-min after RFCA. Longterm suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
0
12
0
3
Order By: Relevance
“…Indeed, when analyzing predictors of adverse outcome in patients with frequent PVCs, in this large cohort study from Voskoboinik et al [ 11 ], patients with structural heart disease were excluded from both validation cohorts. Moreover, Im et al [ 12 ] showed that right ventricular PVC was among the unadjusted predictors of late PVC recurrence; however, the multivariate analysis failed to show that PVC site of origin was among the independent predictors for long-term success. Furthermore, patients with a history of structural heart disease were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when analyzing predictors of adverse outcome in patients with frequent PVCs, in this large cohort study from Voskoboinik et al [ 11 ], patients with structural heart disease were excluded from both validation cohorts. Moreover, Im et al [ 12 ] showed that right ventricular PVC was among the unadjusted predictors of late PVC recurrence; however, the multivariate analysis failed to show that PVC site of origin was among the independent predictors for long-term success. Furthermore, patients with a history of structural heart disease were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In a focal ventricular arrythmia, the site of earliest activation is targeted for ablation, with local EGMs >24 ms prior to the earliest activation of the surface QRS a predictor of long-term success. [ 64 ] Characteristically, the local EGM may also display a reverse polarity pattern on the distal and proximal bipoles of the ablation catheter, often with low amplitude initial components. [ 65 ] However, this finding is not specific, and pseudo-focal patterns may also be present in deep substrate.…”
Section: Mapping During Ventricular Tachycardiamentioning
confidence: 99%
“…Catheter ablation has been established as an important treatment strategy for idiopathic premature ventricular complexes (PVCs). Success rates with PVC ablation can range from 50 to > 90%, and can vary based on PVC sites of origin, electrophysiological characteristics, ablation techniques, as well as operator experience [1]. Among the different reported locations, PVCs originating from the ventricular outflow tract (OT-PVCs) are the most commonly seen, and similarly have been the most studied [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%